2021
DOI: 10.3389/fimmu.2021.640672
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells Generated From Human Induced Pluripotent Stem Cells Mature to CD56brightCD16+NKp80+/-In-Vitro and Express KIR2DL2/DL3 and KIR3DL1

Abstract: The differentiation of human induced pluripotent stem cells (hiPSCs) into T and natural killer (NK) lymphocytes opens novel possibilities for developmental studies of immune cells and in-vitro generation of cell therapy products. In particular, iPSC-derived NK cells gained interest in adoptive anti-cancer immunotherapies, since they enable generation of homogenous populations of NK cells with and without genetic engineering that can be grown at clinical scale. However, the phenotype of in-vitro generated NK ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Ex vivo-induced CD49a + iNK cells can mimic dNK cell function in vivo. Several attempts have been made to expand NK cells with phenotypic similarities to dNK cells (27,53). However, it is unclear whether these NK cells induced by different pathways have in vivo functions that promote embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo-induced CD49a + iNK cells can mimic dNK cell function in vivo. Several attempts have been made to expand NK cells with phenotypic similarities to dNK cells (27,53). However, it is unclear whether these NK cells induced by different pathways have in vivo functions that promote embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, about 5-15% of lymphocytes are defined as NK cells in peripheral blood, and tissue-specific subpopulations are found in the spleen, liver, and lung (57)(58)(59)(60)(61). Generally, human NK cells can be divided into two subpopulations by the expression of CD56 and CD16 on the cell membrane (62,63). About 90% of all NK cells in human peripheral blood are CD56 dim CD16 bright , whereas only 10% are CD56 bright CD16 -/dim (64).…”
Section: Nk Cells Play a Role In Antimicrobial Responsesmentioning
confidence: 99%
“…Recently, hPSCs have emerged as an alternative cell source for NK cells to address these issues. Due to their innate killing ability, many studies have shown the superior antitumor activities of hPSC-derived NK cells without additional engineering approaches that confer antigen-specific activity [Woll et al, 2005[Woll et al, , 2009Larbi et al, 2012;Hermanson et al, 2016;Zeng et al, 2017;Mat-subara et al, 2019;Zhu et al, 2020a, b;Cichocki et al, 2020;Goldenson et al, 2020;Euchner et al, 2021;Woan et al, 2021;Du et al, 2022;Jung et al, 2022]. A few strategies were developed to enhance in vivo persistence and antitumor activities of hPSC-derived NK cells.…”
Section: Nk Cellsmentioning
confidence: 99%